ANTIVIRAL AND IMMUNE STIMULANT ACTIVITIES OF GLYCYRRHIZIN AGAINST DUCK HEPATITIS VIRUS - Soufy, Hamdy; Yassein, Safaa; Ahmed, Alaa R; Khodier, Mohamed H; Kutkat, Mohamed A; Nasr, Soad M; Okda, Faten A (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
This study was conducted to investigate the effect of glycyrrhizin as an immune stimulant against duck hepatitis virus (DHV). In vitro study was carried out to determine cytotoxic and antiviral effects of glycyrrhizin in VERO cells. In vivo study was performed on 40 one-day-old White Pekin ducklings. –and the birds weres divided into 4 groups: control, glycyrrhizin treated, vaccinated with live attenuated DHV vaccine and glycyrrhizin treated and vaccinated; to investigate the changes in immunity and challenge test. Blood samples were collected from each duckling for evaluation of cellular and humeral immunity. The in vitro results revealed that glycyrrhizin had antiviral and no toxic effects till 106 dilutions. Higher antibody titer was observed from the 5th week till the end of experiment in glycyrrhizin and vaccinated group. Treatment with glycyrrhizin alone or with DHV vaccine demonstrated a pronounced lymphocytic proliferation response after 4 days post-inoculation till the end of experiment, while vaccinated group revealed a pronounced proliferation response after 24 days post-inoculation. Treatment with glycyrrhizin alone or combination with DHV vaccine revealed good immune stimulant and antiviral effect against DHV.